Relationship Between Self-Image and The Tendency of Juvenile Sexual Behavior - Irhamna Hidayati; Taufik Taufik (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon of the number of adolescents who tend to deviate sexual behavior such as holding hands, cuddling kissing to having sex with the opposite sex. Deviant sexual behavior is a negative behavior that is thought to be one of the contributing factors is a low Self-Image. This study aims to examine Self-Image relationships with the tendency of juvenile deviant sexual behavior.This research is a descriptive correlational research with quantitative methods. Sample determined with stratifate random sampling obtained as many 275 students. Data collections instruments are a scale questionnaire. Data is processed using the Pearson product moment formula with the Statical Product abd Service Solution (SPSS) program version 20.0. The results of this study revealed that no relation between Self-Image and deviant sexual behavior, if a high Self-Imagedoes not mean the tendency of sexual behavior to deviate low and vice versa if a low Self-Image does not meanhight sexual behavior. From this study it was revealed that most Self-Images were in the high category as much 41,45%, and deviant sexual behavior in the very low category that is as much 93,82%. Based on the findings of this study, it is expected that the counselor or counselor can provide assistance and services in the form of guidance and counseling services.